Genome-Wide Analysis of Response Regulator Genes in Solanum lycopersicum - Cui, Jun; Jiang, Ning; Meng, Jun; Luan, Yushi (Bioinformatics Research and Applications, 2017)
Using whole genome - wide analysis, we identified 40 response regulator (RR) genes in Solanum lycopersicum. They can be divided into 7 subgroups according the structure characteristics and the sequence similarity and topology. The analyses of gene structure, protein motif, chromosome distribution, gene duplication and comparative phylogenetic analysis are performed in detail. The transcription levels of SlRRs in biotic stresses are further analyzed to obtain the functions information of these genes. Furthermore, qRT - PCR analysis shows 11 SlRRs which may be involved in tomato - Phytophthora infestans interaction, played different roles between resistant and sensitive tomato. Our systematic analyses provide insights into the characterization of SlRRs in tomato and basis for further functional studies of these genes.